2005
DOI: 10.1143/jjap.44.5484
|View full text |Cite
|
Sign up to set email alerts
|

Depth Profile and Line-Edge Roughness of Low-Molecular-Weight Amorphous Electron Beam Resists

Abstract: Guided by the paper [10] by Polyakov and Rychkov, we compute the second variational derivative of a wavy plane Wilson surface observable, to find that a necessary condition for a proposed surface equation to be satisfied in the large-N limit is that we are in the critical dimension D = 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…48,56,57 Recently, molecular glass resists have attracted attention as candidates for high-resolution patterning. [58][59][60][61][62][63][64][65][66][67] Fréchet et al 68 reported EB resist materials based on dendritic polymer resins, resulting in 50-100 nm line and space patterns. Ochiai et al 69 reported negative-type high-resolution resists based on p-chloromethylmethoxycalix [4]arene.…”
Section: Synthesis Of Noria and Its Applications To Eb And Euv Resistmentioning
confidence: 99%
“…48,56,57 Recently, molecular glass resists have attracted attention as candidates for high-resolution patterning. [58][59][60][61][62][63][64][65][66][67] Fréchet et al 68 reported EB resist materials based on dendritic polymer resins, resulting in 50-100 nm line and space patterns. Ochiai et al 69 reported negative-type high-resolution resists based on p-chloromethylmethoxycalix [4]arene.…”
Section: Synthesis Of Noria and Its Applications To Eb And Euv Resistmentioning
confidence: 99%
“…However, there is a serious problem among the resolution of pattern, sensitivity of the photo-chemical reaction, and roughness of the pattern, i.e., these relationships are well known as "trade-off". To overcome this "trade-off", many molecular glasses such as calixarenes, 1-10 dendritic oligomers, [11][12][13][14][15][16][17][18] low-molecular-weight oligomers, 19,20 and fullerenes 21 have been reported and their resolutions showed about 50 nm regions. Recently, we could design a ladder type cyclic oligomer "noria" (noria = water wheel in Latin), 22 and examined the synthesis, physical properties, and patterning properties of noria derivatives with pendant t-butyl ester groups, 23,24 t-butyloxycarbonyl groups, 25 adamantyl ester groups, 26,27 cyclohexyl acetal moiety, 28 and oxetanyl groups 29 using electron beam (EB) or EUV exposure systems.…”
Section: Introductionmentioning
confidence: 99%
“…Work by the Hirayama group at TOK investigated low-molecular-weight polyphenol, 4,4'-methylenebis[2-[di(2-methyl-4-hydroxy-5-cyclohexylphenyl)]methyl]phenol (3MC-MBSA). 2 They demonstrated that the film distribution in the depth direction for resist components. They discussed in detail what influence the resist components of 3MC-MBSA and two different photo-acid generator (PAG) types have on the pattern LER and the film distribution in achieving good resist performance.…”
Section: Introductionmentioning
confidence: 99%